Implementing OSH-MS in North Sumatra's Hospitals and Public Health Centers: Challenges and Best Practices - Herlina J. EL-Matury; Nabila Syahlan; Mohd Rafee B. Baharuddin; Rizliana Anggita (Universitas STRADA Indonesia, 2026)
Background: Occupational Safety and Health Management Systems (OSH-MS) are essential for protecting healthcare workers and ensuring safe service delivery in healthcare facilities. Purpose: This study aimed to assess and compare the implementation of OSH-MS in hospitals and primary health centres using a principle-based framework. Methods: A cross-sectional assessment was conducted in six hospitals and seven primary health centres, evaluating five OSH-MS principles: establishing OHS policies, OSH plans, OHS plan implementation, OHS performance monitoring and evaluation, and OHS performance review and improvement. Data were collected through document review and verification of implementation evidence, and achievement was analysed descriptively as percentages. Results: The results reveal substantial variation in OSH-MS implementation, with overall achievement ranging from 14% to 88%. OSH planning and implementation showed relatively high achievement across most facilities, indicating that operational safety measures are generally in place. In contrast, establishing OHS policies, monitoring and evaluation, and performance review and improvement demonstrated consistently lower achievement, particularly in several primary health centres. Hospitals generally performed better than primary health centres, although variability was observed within both groups. Conclusion: In conclusion, OSH-MS implementation in healthcare facilities remains uneven and predominantly focused on operational activities, with limited emphasis on governance, monitoring, and continuous improvement. Strengthening leadership commitment, formal OHS policies, and systematic monitoring and review mechanisms is necessary to achieve comprehensive and sustainable OSH-MS implementation, especially in primary health care settings.